Pengaruh Motivasi, Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Pt. Satya Mulya Mandiri Bogor - Agung Rizki Awaludin; Samsuri Samsuri; Chandra Ayu Pramestidewi (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to determine the influence of motivation, work environment and discipline on employee performance at PT. Satya Mulya Mandiri Bogor The subjects of the research were 52 employees. Sampling was carried out using saturated samples. The analytical tool used in this research is the IBM SPSS 25 software application. The form of this research is descriptive and verification with a quantitative approach. This research uses multiple linear regression analysis. This research found that motivation, work environment and work discipline partially and simultaneously influence employee performance.